Ways with water - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
One thing is as clear as water: the world needs to manage its water better, and waste less. Gloomy scenarios about water conflicts have drowned out a lot of positive initiatives, hopeful experiments and sound policy steps. Shortages have helped...